Starter Concentration of SSA4 Thermophilic Bacteria in Producing Xylanase - Irdawati Irdawati; Jannah Koftiah; Dwi Hilda Putri; Linda Advinda (Bioscience, 2023)
Advances in the field of biotechnology have led to the use of enzymes in industry increasingly. The high public awareness of environmental pollution makes enzyme technology as an alternative to replace various chemical processes. Enzymes can be used in various industrial sectors such as textiles, food, detergents, paper and cosmetics, as well as biofuels. One of the enzymes that is often used is the enzyme xylanase. Thermophilic microorganisms that can produce thermostable enzymes are thermophilic bacteria. One of the important factors affecting the success of the manufacturing process of the production of the xylanase enzyme is the concentration of the starter. The production of the thermophilic bacterial xylanase enzyme SSA 4 produced the highest specific enzyme activity at a concentration of 4% which was 0.137 U/mg. This shows that low starter concentrations can overwhelm microbial growth well. The increase in the concentration of the starter causes the enzyme activity to decrease, this happens.